2016
DOI: 10.1007/s10584-016-1734-x
|View full text |Cite
|
Sign up to set email alerts
|

Fern species richness and abundance are indicators of climate change on high-elevation islands: evidence from an elevational gradient on Tahiti (French Polynesia)

Abstract: Inherent characteristics of island species make them particularly susceptible to anthropogenic changes and need to be assessed to implement appropriate conservation strategies. The impacts of climate change are increasingly being investigated along elevational gradients since they provide natural laboratories to study how species respond to climatic variation. Ferns are particularly sensitive to air humidity and temperature and are therefore potentially useful as bio-indicators. This study addresses the questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…() found that the level of phylogenetic clustering differed between the life stages and with elevation, with sporophytes showing evidence of phylogenetic clustering that grew stronger with increasing elevation, while gametophytes showed no evidence of phylogenetic clustering at any elevation. These authors also found, strikingly, that gametophytes showed no evidence of the mid‐elevation peak in species richness that is a hallmark of fern species distributions across elevational gradients in the tropics, based entirely on studies of sporophytes (Cardelus et al., ; Kluge and Kessler, ; Watkins et al., ; Kluge et al., ; Kessler et al., ; Pouteau et al., ). These findings together strongly suggest that gametophytes are governed by different assembly rules than are sporophytes.…”
Section: Discussionmentioning
confidence: 99%
“…() found that the level of phylogenetic clustering differed between the life stages and with elevation, with sporophytes showing evidence of phylogenetic clustering that grew stronger with increasing elevation, while gametophytes showed no evidence of phylogenetic clustering at any elevation. These authors also found, strikingly, that gametophytes showed no evidence of the mid‐elevation peak in species richness that is a hallmark of fern species distributions across elevational gradients in the tropics, based entirely on studies of sporophytes (Cardelus et al., ; Kluge and Kessler, ; Watkins et al., ; Kluge et al., ; Kessler et al., ; Pouteau et al., ). These findings together strongly suggest that gametophytes are governed by different assembly rules than are sporophytes.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that including the gametophyte phase may also reveal different patterns from those observed in sporophytes in other transect studies. Pouteau et al (2016) analyzed the same sporophyte plot data as well as island-wide diversity of fern sporophytes on Tahiti, and found that climate seems to explain the observed richness peak better than the mid-domain effect (i.e., species richness peak due to randomly distributed elevational ranges within a bounded space; Colwell and Lees 2000).…”
Section: Fern Community Structure Differs Between Life Stagesmentioning
confidence: 99%
“…Ferns are distributed globally, but they have the highest density in the tropical mountains [4]. Ferns are sensitive to the indicators of environmental conditions [5][6][7][8][9][10], with various adaptative strategies to variations in climatic and edaphic parameters [11,12]. Hence, fern diversity shows clear patterns along environmental gradients at different spatial scales [8,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to many other groups of plants and animals, the taxonomic diversity of fern gradients generally follows a hump-shaped unimodal pattern along the elevational gradient [4,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The main drivers for such unimodal patterns are the combined effects of different climatic factors, including the temperature, precipitation, and cloud cover [4,[8][9][10]21,[27][28][29][30][31][32][33][34][35]. Generally, fern diversity tends to be high in temperate and humid habitats but low in cold, hot, and arid habitats [10,36].…”
Section: Introductionmentioning
confidence: 99%